EXTRAPANCREATIC INFECTIONS IN ACUTE PANCREATITIS AND ITS INFLUENCE ON DISEASE OUTCOME - Majid Abbas Khawaja; Reyaz Ahmed Para2; Mushtaq Ahmad Khan; Adnan Firdous Raina; Sumera Saba (National Journal of Medical Research, 2017)
Introduction: Limited data is available on prevalence of extrapancreatic infection, its influence on outcome of pancreatitis.